2020
DOI: 10.1371/journal.pone.0227204
|View full text |Cite
|
Sign up to set email alerts
|

Management of veterinary anaesthesia in small animals: A survey of current practice in Quebec

Abstract: ObjectiveTo describe how small animal anaesthesia is performed in French-speaking Eastern Canada, and the variations between practices, in particular based on practice type, veterinarian gender and experience. DesignObservational study, survey. Sample 156 respondents. ProcedureA questionnaire was designed to assess current small animal anaesthesia practices in French-speaking Eastern Canada, mainly in the province of Quebec. The questionnaire was available through SurveyMonkey, and consisted of four parts: dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Medetomidine and dexmedetomidine are alpha-2 adrenoreceptor agonists routinely used to produce sedation and analgesia in dogs [ 1 , 2 , 3 , 4 ]. Medetomidine is a racemic mixture of two optical isomers, levomedetomidine and dexmedetomidine [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medetomidine and dexmedetomidine are alpha-2 adrenoreceptor agonists routinely used to produce sedation and analgesia in dogs [ 1 , 2 , 3 , 4 ]. Medetomidine is a racemic mixture of two optical isomers, levomedetomidine and dexmedetomidine [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For inferential statistical analysis, the selected demographic characteristics described in Part I, namely year of graduation and type of practice, were tested as potential risk factors influencing responses in the following sections. These factors were chosen based on the results of a previous study [ 6 ]. Indeed, they were likely to affect the results in the current study as well.…”
Section: Methodsmentioning
confidence: 99%
“…Several guidelines have been published, including recommendations for best practice in pre-anaesthetic work-up, anaesthetic monitoring, and analgesia [ 1 5 ]. A recently published survey described current French-speaking Eastern Canada veterinary anaesthesia management [ 6 ]. The authors concluded that the level of care in French-speaking Eastern Canada failed to meet published guidelines for several criteria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations